The Role of Public Relations in Enhancing Public Trust as Muzakki towards the City of Medan's BAZNAS - Munthe, Putri Oktapiani; Muin, Mohd. Iqbal Abdul A. (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research delves into the pivotal role of Public Relations (PR) in bolstering public trust among prospective muzakki (donors) towards Baznas of Medan City, an official and reputable zakat collection institution. A prevalent concern in the community revolves around determining the rightful recipients of zakat. Should it be directly distributed by muzakki to the mustahiq (those eligible to receive zakat), or should it be channeled through Baznas as the zakat collector? Utilizing a qualitative, descriptive approach, this study is conducted at Baznas of Medan City, situated at Jl. Prajurit No.95, Glugur Darat I, Kec. Medan Tim., Medan City, North Sumatra 20236. Data is collected through observations and interviews with Baznas representatives. The primary objectives of this research are to explore: 1) Baznas' strategies in empowering public relations as the forefront of Baznas in Medan City. 2) The support and management activities provided by Baznas of Medan City in the social and humanitarian sectors to enhance the community's quality and trust as muzakki. 3) The empowerment initiatives that involve direct supervision of zakat management for potential muzakki, which serve as evaluations for Baznas towards its muzakki engagement.